"I Do It With Love": Engagement in Caring for People With Dementia. (29th September 2016) - Todorova, Irina; Turner, Hope; Castaneda-Sceppa, Carmen; Young, David; Bonner, Alice
For caregivers, the impacts of caring for their loved ones with dementia at home are complex. The purpose of this study was to gain understanding of the meaning and experience of engagement for caregivers of individuals with dementia living in the community. Participants are from a culturally diverse population of low-income caregivers and care recipients in the northeastern United States. We conducted in-depth semi-structured interviews with caregivers ( n = 17) who were caring for parents, friends, or other relatives with dementia. We used interpretative phenomenological analysis and identified the superordinate themes of connectedness, meaningfulness, acceptance, and vigilance. We conclude that caregiver engagement is a multidimensional phenomenon, with some dimensions being contextual and specific to caregiving. It is a relational concept, referring to a committed, vigilant, and meaningful relationship of caregivers and care recipients as active collaborators. The different aspects of engagement can complement each other, or they can be in contradiction.